"ineffable power": pierced coins and belief in the latin east. (2nd October 2018) - Weetch, Rosie
Abstract: Using the large collection of crusader coins at the Museum of the Order of St. John as a starting point, this paper explores some of the non-monetary roles that coins played in the crusading world. A significant number show evidence of secondary use, with some being pierced for suspension to be used as items of jewelry. Through this transformation such coins would have lost their monetary value but would have gained new values that were just as powerful. These coins were probably worn as amulets, their effectiveness and power being aided by the materiality, function, and iconography of the coins themselves. This paper argues that in being worn, held, and touched, these repurposed coins were used by individuals in their everyday experience and expression of belief within the changing sociopolitical landscape of the Latin East.